2021
DOI: 10.1002/xrs.3223
|View full text |Cite
|
Sign up to set email alerts
|

Complementary MA‐XRF and μ‐Raman results on two Leonardo da Vinci drawings

Abstract: In 2018 all of Leonardo's drawings and manuscripts belonging to the Biblioteca Reale di Torino were moved to ICRCPAL for a complete scientific characterisation in preparation for the celebrations of the 500th anniversary of the artist's death. Except for the famous Autoritratto that was already studied twice in this manner (2012, 2015), the other drawings and documents had never been subjected to scientific investigations. This paper reports the results of the non‐destructive analysis of two drawings: Studi di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…For instance, art history investigations on Leonardo da Vinci's drawings carried out in the past two decades have successfully integrated analytical measurements to identify constituting materials, delineate the artist's modus operandi, and characterize material deterioration over time [20][21][22]. Suffice to mention Leonardo's drawings belonging to the Biblioteca Reale in Turin, which were recently analyzed with macro X-ray Fluorescence (MA-XRF), μ-Raman spectroscopy, and atomic force microscopy (AFM) to identify their constituting materials and assess their state of conservation [23,24]. This line of research clearly points to the need for further integration of scientific methods to gain a thorough understanding of Leonardo's creative process.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, art history investigations on Leonardo da Vinci's drawings carried out in the past two decades have successfully integrated analytical measurements to identify constituting materials, delineate the artist's modus operandi, and characterize material deterioration over time [20][21][22]. Suffice to mention Leonardo's drawings belonging to the Biblioteca Reale in Turin, which were recently analyzed with macro X-ray Fluorescence (MA-XRF), μ-Raman spectroscopy, and atomic force microscopy (AFM) to identify their constituting materials and assess their state of conservation [23,24]. This line of research clearly points to the need for further integration of scientific methods to gain a thorough understanding of Leonardo's creative process.…”
Section: Introductionmentioning
confidence: 99%
“…The state-of-the-art MA-XRF instrumentation is represented by raster scanning, i.e., mapping acquisition mode, being a time-and space-ordered collection of spectra [36]. MA-XRF is typically adopted for elemental distribution characterization [37][38][39][40][41], and also combined with several other techniques [42,43] and specific data handling [44]. Indeed, even though there are works exploiting X-ray as radiation to perform stratigraphic studies [27,[45][46][47][48][49][50][51], MA-XRF has never been devoted to the determination of layer thickness.…”
Section: Research Aimmentioning
confidence: 99%
“…A multi-method approach is often used in cultural heritage applications to elucidate the objects under investigation such as drawings, manuscripts and paintings. Bicchieri et al 96 reported the results of the non-destructive analysis of two drawings: Studi di gambe virili and Autoritratto . The use of three complementary techniques (macroXRF spectrometry, μRaman spectroscopy and AFM) with different penetration capabilities gave a complete chemical characterisation of the artworks.…”
Section: Cultural Heritage Applicationsmentioning
confidence: 99%